STRATEGI CALON KEPALA DAERAH PEREMPUAN DALAM KONTESTASI POLITIK DI KOTA BATU TAHUN 2017 - Rika Novitasari; Tikka Dessy Harsanti (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
This study aims to describe strategies for prospective female Regional Heads in various socio-cultural limitations of patriarchy. Using descriptive qualitative research methods, this study seeks to present data on the strategy of female regional head candidates in the Regional Head Elections of Batu City, 2017. DewantiRumpoko as a female regional head candidate in the Batu City Election is quite active in attracting support from women to vote for her in this political contest. His efforts produced results with his election as Mayor of Batu elected for the period 2017-2022. Some efforts such as blusukan (observation) or attending face to face with citizens, determining strategic work programs based on gender mainstreaming, approaches based on household needs, special attention and care of a woman who prioritizes deep feelings and imaging as a strong, and independent woman became the right strategy done by Dewanti Rumpoko.